Low-alkalinity sintering control method and system
By measuring the liquid phase fluidity and bonding phase strength of iron ore powder, a comprehensive score was formed, and the iron ore powder with high scores and low scores was mixed and granulated, which solved the problem of bonding phase changes when the alkalinity of sintered ore decreased, and achieved high yield and low combustion consumption of low alkalinity sintered ore.
Patent Information
- Application Number
- CN202510029253.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-05-02
AI Technical Summary
When the existing sintering process reduces the alkalinity of sintered ore, it faces challenges brought about by changes in the bonding phase system and quantity, resulting in downward fluctuations in sintering indicators and affecting the yield rate.
By measuring the liquid phase fluidity index Y and the bonding phase strength index Q of the iron ore powder, a comprehensive score Z3 is formed, which is divided into high- and low-score iron ore powder, and mixed with fuel, flux, and rebate to form a high-alkaline mixture and a natural alkalinity matrix material, and mixed it into a sintered material with an alkalinity below 1.8 in a certain proportion for sintering.
Low alkalinity control of sintered ore is achieved, the yield rate and solid fuel consumption of sintered ore are improved, and the stability and efficiency of sintering process are improved.
Smart Images

Figure CN119913354A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of computational sintering, and more specifically, the present invention relates to a low-basicity sintering control method and system. Background Art
[0002] The sintering process has developed from low alkalinity to high alkalinity sintering, and the bonding phase system has gradually developed from the initial olivine or silicate system to the calcium ferrite system, which has brought about a comprehensive improvement in the physical, chemical and metallurgical properties of the sintered ore. When the alkalinity is low, the total amount of the bonding phase of the sintered ore is small, which is not conducive to the formation of calcium ferrite, and the bonding phase strength is not high. The strength of the sintered ore is poor.
[0003] At present, most steel companies control the basicity of sintered ore above 1.80. Many companies have also increased the proportion of sintered ore in blast furnaces to temporarily cope with production organization, thereby reducing the basicity of sintered ore to below 1.8. When the basicity is gradually reduced from the current high level, the sintering process needs to face the pain and challenges brought about by changes in the bonding phase system and quantity, and the sintering indicators also fluctuate downward.
[0004] The binary basicity of sintered ore R = CaO / SiO2. There are three traditional routes to reduce the binary basicity R of sintered ore. Reducing the CaO content will lead to a significant decrease in the content of calcium ferrite in the mineral phase, affecting the formation of the sintered ore liquid phase; increasing the SiO2 content will lead to a significant increase in the content of silicate in the mineral phase, resulting in poor strength of the sintered ore; reducing the CaO content and increasing the SiO2 content in parallel will reduce the calcium ferrite content and increase the silicate content. From the perspective of mineralization mechanism, the deterioration index caused by the increase of silicate phase is significantly higher than that caused by the decrease of calcium ferrite, affecting the yield of sintered ore. Summary of the invention
[0005] The present invention provides a low-basicity sintering control method, aiming to improve at least one of the above problems.
[0006] The present invention is achieved by a low-basicity sintering control method, which is specifically as follows:
[0007] (1) Determine the liquid phase fluidity index Y and bonding phase strength index Q of various iron ore powders at the production site;
[0008] (2) Based on the liquid phase fluidity index Y and the bonding phase strength index Q, the liquid phase fluidity score Z1(Y) and the bonding phase strength score Z2(Q) of the corresponding iron ore powder are formed, and then the comprehensive score Z3 of each type of iron ore powder is formed:
[0009] (3) mixing the iron ore powder with a high comprehensive score Z3 with fuel, flux, and return ore to form a mixed material with high basicity, and mixing the iron ore powder with a low comprehensive score Z3 with a binder to form a matrix material with natural basicity;
[0010] (4) The base material and the mixed material are mixed in a certain ratio to form a sintering material with a basicity lower than 1.8, and the sintering material is distributed, ignited, and sintered.
[0011] Furthermore, the test process of the liquid phase fluidity index Y of the iron ore powder is as follows:
[0012] The iron ore powder was measured by X-ray fluorescence spectrometry to determine the contents of CaO and SiO2 in the iron ore pulverization. The dried iron ore powder was ground in a ball mill until the particle size was below -200 mesh. Pure CaO powder was added to the iron ore powder so that the mass ratio of CaO to SiO2 in the iron ore powder reached 4.0. After uniform mixing, a set weight of iron ore powder was put into a sample press to form a sample of a specified particle size. The area of the sample was S1. The sample was put into an iron ore high-temperature characteristic furnace and roasted at a set temperature for a set time. The flow area S2 in the sintered sample was measured, and the liquid phase fluidity index Y=S2 / S1.
[0013] Further, the test process of the bonding phase strength index Q of iron ore powder is as follows:
[0014] The iron ore powder is measured by X-ray fluorescence spectrometry to determine the contents of CaO and SiO2 in the iron ore pulverization. The dried iron ore powder is ground in a ball mill until the particle size of the iron ore powder is below -200 mesh. Pure CaO powder is added to the iron ore powder so that the mass ratio of CaO to SiO2 in the iron ore powder reaches 2.0. After uniform mixing, a set weight of iron ore powder is taken and placed in a sample press to form a sample of a specified particle size. The sample is placed in an iron ore high-temperature characteristic furnace and roasted at a set temperature for a set time. The strength index of the sintered sample is measured, which is the bonding phase strength index Q of the corresponding iron ore powder.
[0015] Furthermore, based on the liquid phase fluidity index Y, the liquid phase fluidity score Z1(Y) of the corresponding iron ore powder is formed. The calculation formula of the liquid phase fluidity score Z1(Y) is as follows:
[0016]
[0017] Furthermore, based on the bonding phase strength index Q, a bonding phase strength score Z2(Q) corresponding to the iron ore powder is formed. The calculation formula of the bonding phase strength score Z2(Q) is as follows:
[0018]
[0019] Furthermore, the comprehensive score Z3, Z3 = α·Z1(Y)+β·Z2(Q), where α and β are weight coefficients.
[0020] Furthermore, the alkalinity of the mixture is between 1.9 and 2.3.
[0021] Furthermore, the basicity of the base material is between 0.1 and 0.8.
[0022] The present invention is implemented as follows: a low-basicity sintering control system, the system comprising: an input unit, a processing unit and an output unit connected in sequence;
[0023] An input unit is used to input the measured liquid phase fluidity index Y and bonding phase strength index Q of various iron ore powders at the production site;
[0024] A processing unit, which determines the iron ore powder used to form a high-basicity mixed material and a low-basicity matrix material based on the low-basicity sintering control method, and outputs the iron ore powder through an output unit;
[0025] The corresponding iron ore powder is mixed with fuel, flux and return ore once and twice to form a mixture, the corresponding iron ore powder is mixed with a binder to form granules to form a base material, the base material and the mixture are mixed in a certain proportion to form a sintering material with an alkalinity of less than 1.8, the sintering material is distributed, ignited and sintered to form a low-alkalinity sintered ore.
[0026] The low-basicity sintered ore control method provided by the present invention has the following beneficial technical effects:
[0027] (1) The existing sintering consolidation is mainly liquid phase. The present invention is to form a sintered ore matrix material of a certain particle size by granulating the concentrate and the binder separately, mainly with solid phase bonding. Preferably, the powder ore, flux, fuel and return ore are mixed and granulated to form a traditional mixed material. A large amount of liquid phase is generated during the sintering process, which wraps the matrix material.
[0028] (2) The iron ore powder for sintering is scored and sorted according to the liquid phase fluidity index and the bonding phase strength. The high-scoring concentrate and powder ore are mixed into a high-alkalinity mixture according to the ore blending structure. During the sintering process, more liquid phase is generated. The ore phase structure is mainly needle-shaped calcium ferrite, and the bonding phase strength is high. The low-scoring concentrate and binder are mixed and granulated separately on a disc to form a natural alkalinity matrix material. The ratio of the matrix material and the mixture is controlled to facilitate mutual wrapping. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A flow chart of a method for controlling a sintered ore with low basicity provided by an embodiment of the present invention;
[0030] Figure 2 A schematic diagram of the structure of the composite material provided by an embodiment of the present invention;
[0031] Figure 3 A schematic structural diagram of a low-basicity sintered ore control system provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0032] The specific implementation modes of the present invention are further explained in detail below by describing the embodiments with reference to the accompanying drawings, so as to help those skilled in the art to have a more complete, accurate and in-depth understanding of the inventive concept and technical solution of the present invention.
[0033] Figure 1 The flow chart of the low basicity sintering control method provided by the embodiment of the present invention is as follows:
[0034] (1) Determine the liquid phase fluidity index Y and bonding phase strength index Q of various iron ore powders at the production site;
[0035] In the embodiment of the present invention, if there is Class A iron ore powder at the production site, it is necessary to measure the liquid phase fluidity index Y and the bonding phase strength index Q of each type of iron ore powder, and the specific test process is as follows:
[0036] (11) Testing process of liquid phase fluidity index Y of iron ore powder:
[0037] The iron ore powder was measured by X-ray fluorescence spectrometry to determine the contents of CaO and SiO2 in the iron ore powder. The dried iron ore powder was ground by a ball mill until the particle size of the iron ore powder was below -200 mesh. Pure CaO powder was added to the iron ore powder to make the mass ratio of CaO to SiO2 in the iron ore powder reach 4.0. After uniform mixing, 1.25 g of the iron ore powder was taken and put into a sample press to form a cylindrical cake sample with a particle size (diameter) of 10 mm. The area of the cylindrical cake sample was S1 = 25πmm 2 , put the cylindrical cake sample into the iron ore high temperature characteristic furnace, sinter it at the set temperature for the set time, take out the sintered cylindrical cake sample, measure the flow area S2 in the cylindrical cake sample, and the liquid phase fluidity index is Y=S2 / S1.
[0038] (12) Testing process of bonding strength index Q of various iron ore powders:
[0039] The iron ore powder was measured by X-ray fluorescence spectrometry to determine the contents of CaO and SiO2 in the iron ore pulverization. The dried iron ore powder was ground in a ball mill until the particle size of the iron ore powder was below -200 mesh. Pure CaO powder was added to the iron ore powder so that the mass ratio of CaO to SiO2 in the iron ore powder reached 2.0. After uniform mixing, 1.25 g of the iron ore powder was put into a sample press to form a cylindrical cake sample with a particle size (diameter) of 10 mm. The cylindrical cake sample was put into an iron ore high-temperature characteristic furnace. After roasting at a set temperature for a set time, the sintered cylindrical cake sample was taken out and the strength index of the cylindrical cake sample was measured, which was the bonding phase strength index Q of the corresponding iron ore powder.
[0040] The temperature and time set in the high temperature characteristic furnace of iron ore in the test of liquid phase fluidity index Y are the same as the temperature and time set in the high temperature characteristic furnace of iron ore in the test of bonding phase strength index, and the temperature is generally set at 1350°C.
[0041] (2) Based on the liquid phase fluidity index Y and the bonding phase strength index Q, the liquid phase fluidity score Z1(Y) and the bonding phase strength score Z2(Q) of the corresponding iron ore powder are formed, and then the comprehensive score Z3 of each type of iron ore powder is formed. The liquid phase fluidity performance is the ability of the iron ore powder to react with the flux to generate a liquid phase. During the sintering ore blending process, it is necessary to complement the advantages and disadvantages of the ore types to prevent the liquid phase fluidity from being too poor. Based on the comprehensive consideration of the differences in the production equipment capabilities of steel enterprises and the economic efficiency of iron ore powder, the liquid phase fluidity of the sintered ore is controlled at 2.6-3.2, and the single ore iron ore powder is evaluated according to the sintered ore liquid phase fluidity control standard. Based on the liquid phase fluidity index Y, the liquid phase fluidity score Z1(Y) of the corresponding iron ore powder is formed. The calculation formula of the liquid phase fluidity score Z1(Y) is as follows:
[0042]
[0043] The bonding phase strength indicates the strength of the liquid phase formed during the sintering process of iron ore to consolidate the surrounding core particles. Under certain conditions such as sintering process parameters, assimilation of the mixed ore, and liquid phase fluidity, ore blending with the goal of achieving the highest possible strength of the bonding phase of the mixed ore will help improve the consolidation strength of the sintered ore. However, based on the economic benefits of long-term contract ores and market ores, the bonding phase strength value of sintered ore between 830N and 920N is suitable for low-cost and high-quality production by steel companies. Single-ore iron ore powder is evaluated according to the bonding phase strength of the sintered ore. Based on the bonding phase strength index Q, the bonding phase strength score Z2(Q) of the corresponding iron ore powder is formed. The calculation formula for the bonding phase strength score Z2(Q) is as follows:
[0044]
[0045] The liquid phase fluidity score Z1(Y) and the bonding strength score Z2(Q) of each type of iron ore powder are weighted to obtain the comprehensive score Z3 of each type of iron ore powder, Z3=α·Z1(Y)+β·Z2(Q), wherein α and β are weight coefficients, and α+β=1.
[0046] (3) mixing the iron ore powder with a high comprehensive score Z3 with fuel, flux, and return ore to form a mixed material with high basicity, and mixing the iron ore powder with a low comprehensive score Z3 with a binder to form a matrix material with natural basicity;
[0047] In the embodiment of the present invention, the total score Z3 of various iron ore powders at the production site is arranged in order from high to low; each type of iron ore powder includes powder ore with larger particle size and concentrate ore with smaller particle size, and the iron ore powder with the highest ranking or the powder ore corresponding to the iron ore powder is mixed with fuel, flux, and return ore once and twice to form a mixture with higher alkalinity, and the alkalinity of the mixture is between 1.9 and 2.3. The concentrate iron ore powder with the lowest ranking is mixed with a binder on a disc to form a base material with natural alkalinity, and the alkalinity of the base material is between 0.1 and 0.8.
[0048] In an embodiment of the present invention, there is Class A iron ore powder at the production site, the first b*A iron ore powders in the sorted iron ore powders are used to form a mixed material, and the last (1-b)*A iron ore powders in the sorted iron ore powders are used to form a matrix material, and b is a set ratio.
[0049] (4) The base material and the mixed material are mixed in a certain ratio to form a sintering material with a basicity lower than 1.8, and the sintering material is distributed, ignited, and sintered to form a sintered ore.
[0050] In the embodiment of the present invention, the base material and the mixed material are mixed to form a composite material such as Figure 2 As shown, the inner pellets are base material, and the surrounding of the base material is mixed material.
[0051] The present invention forms a comprehensive score based on the liquid phase fluidity and bonding phase strength of the iron ore, selects iron ore powder with a high comprehensive score to form a mixture, and uses a high-alkalinity mixture with liquid phase fluidity and bonding phase strength to wrap low-alkalinity pellets (matrix material) with solid phase bonding to form a high-strength sintering material. The alkalinity of the sintering material is lower than that of traditional sintering materials, and the solid fuel consumption is low, which improves the yield of sintered ore. The comprehensive alkalinity of the sintered ore can reach 1.35-1.75, thereby achieving extremely high efficiency of sintering capacity and a high proportion of sintered ore used in blast furnaces.
[0052] Figure 3 A schematic diagram of the structure of a low-basicity sintering control system provided by an embodiment of the present invention. For ease of description, only the parts related to the embodiment of the present invention are shown. The system includes: an input unit, a processing unit, and an output unit connected in sequence;
[0053] An input unit is used to input the liquid phase fluidity index Y and the bonding phase strength index Q of various iron ore powders measured at the production site; a processing unit is used to determine the iron ore powders used to form a high-basicity mixture and a low-basicity matrix material based on the above-mentioned low-basicity sintering control method, and output them through an output unit;
[0054] The corresponding iron ore powder is mixed with fuel, flux and return ore once and twice to form a mixture, the corresponding iron ore powder is mixed with a binder to form granules to form a base material, the base material and the mixture are mixed in a certain proportion to form a sintering material with a basicity of less than 1.8, and the sintering material is distributed, ignited and sintered to form a sintered ore.
[0055] The method of the present invention was used to test the liquid phase generation ability and bonding phase strength of 10 kinds of iron ore powders in the sintering batching scheme of a steel plant, and then the liquid phase fluidity and bonding phase strength of the iron ore types were scored, as shown in Table 1.
[0056] Table 1 Comprehensive score of iron ore powder
[0057]
[0058] The concentrates of mines 9 and 10 were mixed with bentonite on a disc at a moisture content of 8.5% and granulated. A base material of 8-10 mm was selected, and the natural alkalinity of the base material was 0.16.
[0059] Ore 1, Ore 2, Ore 3, Ore 4, Ore 5, Ore 6, Ore 7, Ore 8, solvent, fuel and return ore are mixed once at a moisture content of 6.1%, and then mixed and granulated twice to form a mixture, and the alkalinity is controlled to be 2.25.
[0060] The base material and the mixed material are mixed in a mass ratio of 1:2, and the basicity of the mixed sintered material is 1.53. The mixed comprehensive material is distributed and sintered to obtain the finished sintered ore. Compared with the traditional sintered ore, the new sintered ore has a lower solid fuel consumption and a higher yield rate, as shown in Table 2.
[0061] Table 2 Sintering indicators
[0062]
[0063] The present invention has been described exemplarily. Obviously, the specific implementation of the present invention is not limited to the above-mentioned method. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A low basicity sintering control method, characterized in that: The method is specifically as follows: (1) Determine the liquid phase fluidity index Y and bonding phase strength index Q of various iron ore powders at the production site; (2) Based on the liquid phase fluidity index Y and the bonding phase strength index Q, the liquid phase fluidity score Z1(Y) and the bonding phase strength score Z2(Q) of the corresponding iron ore powder are formed, and then the comprehensive score Z3 of each type of iron ore powder is formed: (3) mixing the iron ore powder with a high comprehensive score Z3 with fuel, flux, and return ore to form a mixed material with high basicity, and mixing the iron ore powder with a low comprehensive score Z3 with a binder to form a matrix material with natural basicity; (4) The base material and the mixed material are mixed in a certain ratio to form a sintering material with a basicity lower than 1.8, and the sintering material is distributed, ignited, and sintered.
2. The low-basicity sintering control method according to claim 1, characterized in that: The testing process of the liquid phase fluidity index Y of iron ore powder is as follows: The iron ore powder was measured by X-ray fluorescence spectrometry to determine the contents of CaO and SiO2 in the iron ore pulverization. The dried iron ore powder was ground in a ball mill until the particle size was below -200 mesh. Pure CaO powder was added to the iron ore powder so that the mass ratio of CaO to SiO2 in the iron ore powder reached 4.
0. After uniform mixing, a set weight of iron ore powder was put into a sample press to form a sample of a specified particle size. The area of the sample was S1. The sample was put into an iron ore high-temperature characteristic furnace and roasted at a set temperature for a set time. The flow area S2 in the sintered sample was measured, and the liquid phase fluidity index Y=S2 / S1.
3. The low-basicity sintering control method according to claim 1, characterized in that: The test process of the bonding phase strength index Q of iron ore powder is as follows: The iron ore powder is measured by X-ray fluorescence spectrometry to determine the contents of CaO and SiO2 in the iron ore pulverization. The dried iron ore powder is ground in a ball mill until the particle size of the iron ore powder is below -200 mesh. Pure CaO powder is added to the iron ore powder so that the mass ratio of CaO to SiO2 in the iron ore powder reaches 2.
0. After uniform mixing, a set weight of iron ore powder is taken and placed in a sample press to form a sample of a specified particle size. The sample is placed in an iron ore high-temperature characteristic furnace and roasted at a set temperature for a set time. The strength index of the sintered sample is measured, which is the bonding phase strength index Q of the corresponding iron ore powder.
4. The low-basicity sintering control method according to claim 1, characterized in that: Based on the liquid phase fluidity index Y, the liquid phase fluidity score Z1(Y) of the corresponding iron ore powder is formed. The calculation formula of the liquid phase fluidity score Z1(Y) is as follows:
5. The low-basicity sintering control method according to claim 1, characterized in that: Based on the bonding phase strength index Q, the bonding phase strength score Z2(Q) of the corresponding iron ore powder is formed. The calculation formula of the bonding phase strength score Z2(Q) is as follows:
6. The low-basicity sintering control method according to claim 1, characterized in that: Comprehensive score Z3, Z3 = α·Z1(Y)+β·Z2(Q), where α and β are weight coefficients.
7. The low-basicity sintering control method according to claim 1, characterized in that: The alkalinity of the mixture is between 1.9 and 2.
3.
8. The low-basicity sintering control method according to claim 1, characterized in that: The basicity of the base material is between 0.1 and 0.
8.
9. A low-basicity sintering material control system, characterized in that: The system comprises: an input unit, a processing unit and an output unit connected in sequence; An input unit is used to input the measured liquid phase fluidity index Y and bonding phase strength index Q of various iron ore powders at the production site; A processing unit, which determines the iron ore powder used to form a high-basicity mixed material and a low-basicity matrix material based on the low-basicity sintering control method according to any one of claims 1 to 8, and outputs it through an output unit; The corresponding iron ore powder is mixed with fuel, flux and return ore once and twice to form a mixture, the corresponding iron ore powder is mixed with a binder to form granules to form a base material, the base material and the mixture are mixed in a certain proportion to form a sintering material with a basicity lower than 1.8, and the sintering material is distributed, ignited and sintered.
Citation Information
Patent Citations
Manufacturing method of low-alkalinity agglomerate
CN102399979A
Method for preparing blast furnace ironmaking burden from full-vanadium titanium magnetite concentrate
CN103103347A
Method for evaluating fluidity of liquid phases of iron ore powder
CN106769661A
Method for determining characteristic number of bonding strength of sintered ores
CN107101898A
Sintering mixing method for improving strength of sintering drum
CN116377214A
Cited By
Determination method for consolidation capacity of coarse-particle iron ore and sintering initial liquid phase
CN120721566A